SUSTAINABILITY REPORTING AND ESG DISCLOSURE QUALITY IN THE ERA OF DIGITAL ACCOUNTING TRANSFORMATION - Prastika Suwandi Tjeng; Rina Nopianti; Bella Putrie Nindyawan (CV. Lafadz Jaya, 2026)
Digital accounting transformation has shifted the paradigm of corporate reporting through the application of several digital technologies that might raise the standard of information about sustainability. This modification encourages businesses to create Environmental, Social, and Governance (ESG) disclosures and sustainability reports that are more accurate, transparent, and in accordance with stakeholder demands. This study aims to analyze the role of digital accounting transformation in improving the quality of sustainability reporting and ESG disclosures through a literature review approach. The research method uses a literature study by reviewing various reputable scientific articles, books, and relevant academic documents regarding digital accounting transformation, the caliber of ESG disclosures and sustainability reporting. The study's findings show that the use of digital technologies including blockchain, cloud accounting, intelligence, and big data analytics, and integrated reporting systems, can improve data accuracy, information transparency, report preparation speed, verification process effectiveness, and compliance with sustainability reporting standards. On the other hand, the quality of ESG disclosures is still influenced by various challenges, including organizational readiness, data governance, cybersecurity, human resource competency, and evolving regulatory dynamics. Therefore, successful digital accounting transformation requires synergy between technological innovation, good corporate governance, and sustainability strategies to produce more credible, relevant, and decision-supporting ESG reporting. This research provides a conceptual contribution to enriching the literature discusses the connection between raising the standard of sustainability reporting in the digital age and digital accounting transformation.